SISTEM INFORMASI WISATA BERBASIS WEBSITE MENGGUNAKAN METODE PROTOTYPE - Marchel Antonius Sirait; Arief Ichwani (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2023)
Tourism activities cannot be missed, they are a basic need for every human being to eliminate boredom every day. The tourism sector plays an important role for Indonesia, which is currently growing in various regions. By combining information technology and natural resource development business is a form of domestic tourism development strategy. The problem that often occurs when tourists are going on a tour is they lack information on the right location and estimated prices when traveling on the Thousand Islands. As we know, the tour package booking system is still conventional, customers still have to come to the crossing port and the payment system still uses cash. To overcome this problem, an information system was created to facilitate ordering tour packages online which aims to expand marketing and increase profits in the tourism sector. This website-based information system is built using the prototype method. In designing this information system using the PHP programming language, and using the Laravel framework as coding, for the database using MySQL. The results of this study are a tourist information system that can present complete tourist information, order tour packages online, pay using payment gateways, and manage visitor data more quickly and accurately.